The Sociology of Language and Religion - Omoniyi, Tope. author. aut Link
XIII, 241 p.
Keywords: This is an eclectic collection of essays which successfully demonstrate how the Sociology of Language and Religion as a disciplinary paradigm responds to change, conflict and accommodation. The multiple religious coverage in the essays (Judaism, Christianity, Islam) as well as more or less global panorama.